The controversy of esophageal carcinosarcoma: A case report and brief review of literature. Issue 10 (March 2019) - Xu, Xiaoyang; Xu, Yan; Wang, Jiang; Zhao, Can; Liu, Chang; Wu, Bin; Gao, Lei; Dai, Guangquan; Dai, Dongqiu
Abstract: Rationale: Esophageal carcinosarcoma (ECS) is defined as a relatively rare malignant neoplasm with both epithelial carcinomatous and sarcomatous components. Besides, there were so many various controversies in ECS. This article describes a case of ECS that was effectively treated with radical esophagectomy and adjuvant chemotherapy. Also, we discuss the presentation, differential diagnosis, treatment, and prognosis of ECS. Patient concerns: A 58-year-old man presented with a history of progressive dysphagia and precordial pain after swallowing for 1 month. Diagnosis: Esophagogastroduodenoscopy (EGD) revealed a large polypoid neoplasm that occupied the esophageal lumen 30 to 34 cm from the incisors. On the characteristic morphology, clinical symptom and biopsy findings, the ECS was the primary considerated. Computed tomography (CT) examination demonstrated no radiological evidence of metastatic disease. Interventions: The patient underwent an Ivor Lewis esophagectomy, coupled with adequate lymph node dissection (2-field lymphadenectomy). ECS was confirmed by pathology report of postoperative. Then, the patient underwent adjuvant chemotherapy with docetaxel, oxaliplatin, and capecitabine. Outcomes: The patient remained alive without tumor recurrence at 24 months after multidisciplinary therapy. Lessons: It is generally treated by surgery, radiotherapy, and chemotherapy according to the protocols used for other esophageal cancers (EC). However, there is no recommended clinical treatment for ECS because of the rarity of the disease. Esophagectomy with extended lymphadenectomy followed by adjuvant chemotherapy with docetaxel, oxaliplatin, and capecitabine may be recommended treatment for ECS. Chemotherapy regimen with docetaxel, oxaliplatin, and capecitabine may be a suitable adjuvant therapy for ECS.